2008
DOI: 10.1103/physrevlett.100.054501
|View full text |Cite
|
Sign up to set email alerts
|

Micrometric Granular Ripple Patterns in a Capillary Tube

Abstract: The oscillatory motion of a fluid carrying micron-sized particles inside a capillary tube is investigated experimentally. It is found that initially uniformly distributed particles can segregate and accumulate to form regularly spaced micron-sized particle clusters. The wavelength of the microclusters is compared to data for macroscale sand-ripple patterns and found to obey the same universal scaling as these. A dimensional analysis is performed that confirms the universality of the experimentally observed sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…While further analysis of these phenomena extends beyond the scope of this paper, pattern formation, migration and mixing in microfluidic multi-phase flows have been investigated extensively in wide range of biomedical and chemical engineering applications (Gunther and Jensen, 2006). Recently,Zoueshtiagh et al (2008) has reported experimental study of micro granular ripple pattern formation in oscillating two-phase flow.…”
Section: Resultsmentioning
confidence: 99%
“…While further analysis of these phenomena extends beyond the scope of this paper, pattern formation, migration and mixing in microfluidic multi-phase flows have been investigated extensively in wide range of biomedical and chemical engineering applications (Gunther and Jensen, 2006). Recently,Zoueshtiagh et al (2008) has reported experimental study of micro granular ripple pattern formation in oscillating two-phase flow.…”
Section: Resultsmentioning
confidence: 99%
“…Note that viscous flow is also relevant to some engineering applications (Schaflinger, Acrivos & Stibi 1995;Wallner & Schaflinger 1998;Charru & Mouilleron-Arnould 2002). In particular, observations of ripple formation under oscillatory flow in a capillary tube have been reported by Zoueshtiagh et al (2008), in connection with microfluidic issues. In the experiments to be presented, it appeared first that the direction of the observed drift of fluid particles was opposite to the one expected.…”
Section: Introductionmentioning
confidence: 90%
“…In comparison, however, the low-frequency regime is much less explored. Particle collection in the form of ripples in closed systems through pulsating fields has been demonstrated [35][36][37], while in open systems particle movement is triggered by the formation of capillary waves at the liquid-air interface, causing floating particles to accumulate at the nodes and antinodes of the capillary wave, depending on their hydrophobicity [38], and sedimented particles to be collected due to inertial effects at locations dictated by the gradient of the flow field in rectangular chambers [39,40] and in droplets [41].…”
Section: Introductionmentioning
confidence: 99%